A new sampling-based four-terminal-pair digital impedance bridge. (December 2021) - Musioł, Krzysztof; Kampik, Marian; Koszarny, Maciej
Abstract: This paper describes new realization of a sampling-based four-terminal-pair digital impedance bridge and test measurements performed with it. The bridge is based on a new two-channel high-stability digitally synthesized source and a commercial PXI synchronous sampling system. The bridge is capable of comparing any two impedances, regardless of type (R–C, R-L, or L-C), over a large frequency range (from 20 Hz to 20 kHz). Comparisons at 1 kHz and 1592 Hz in the impedance range from several hundred Ω to several kΩ give ratio errors at the level 10 −6 for any kind of impedances, with potential for further improvements.